Proceedings of the Thirteenth ACM Conference on Hypertext and Hypermedia 2002
DOI: 10.1145/513338.513345
|View full text |Cite
|
Sign up to set email alerts
|

Map-based horizontal navigation in educational Hypertext

Abstract: This paper discusses the problem of horizontal (non-hierarchical) navigation in modern educational courseware. We will look at why horizontal links disappear, how to support horizontal navigation in modern hyper-courseware, and our earlier attempts to provide horizontal navigation in Web-based electronic textbooks. Here, we present map-based navigation -a new approach to support horizontal navigation in open corpus educational courseware that we are currently investigating. We will describe the mechanism behin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
1

Year Published

2002
2002
2008
2008

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 20 publications
(15 reference statements)
0
39
0
1
Order By: Relevance
“…The functionality and the usefulness of our map-based information access approach was evaluated it in the context of a real Programming and Data Structures course at the University of Pittsburgh. The characteristics of the SOM, the implementation details of the KnowledgeSea system, and some results of this study were reported in [1]. We were very encouraged to find that about 2/3 of the 21 students participated in the study thought that the system has achieved the goal of providing an access to the online C tutorials completely or "quite well".…”
Section: The Knowledgesea Approachmentioning
confidence: 99%
“…The functionality and the usefulness of our map-based information access approach was evaluated it in the context of a real Programming and Data Structures course at the University of Pittsburgh. The characteristics of the SOM, the implementation details of the KnowledgeSea system, and some results of this study were reported in [1]. We were very encouraged to find that about 2/3 of the 21 students participated in the study thought that the system has achieved the goal of providing an access to the online C tutorials completely or "quite well".…”
Section: The Knowledgesea Approachmentioning
confidence: 99%
“…While community-based hypertext linking approaches have not been analyzed, they do exist [5; 66]; the authors have simply failed to find an example of these approaches, used in an appropriate context. [58]; CoWeb [24] KBS-Hyperbook [32]; SIGUE [18] Keywordbased Knowledge Sea [14] MT Tutor [58] Metadatabased COHSE [19]; Flamenco [67] PRF [30] Communitybased Bollen & Heylighen [5] CoWeb [24]; Knowledge Sea II [9] It is important to stress again that these approaches do not contradict but rather complement other since they have different strong and weak sides. So far, a number of existing systems have combined different approaches to hypertext construction and navigation support.…”
Section: Discussionmentioning
confidence: 99%
“…Thus the application of SOM turns a collection of documents into a structured spatial hypertext (spatial hypertext implies implicit links between spatially co-located documents [57]). Using map-based navigation, introduced in [14], this spatial hypertext can be converted into a regular hyperspace that allows navigation from a document to the hosting map cell and then to similar documents. This technology has been applied in the Knowledge Sea II system, presented below.…”
Section: Keyword-based Techniques For Automatic Hyperspacementioning
confidence: 99%
See 2 more Smart Citations